A lifeline to treatment: the role of Indian generic manufacturers in supplying antiretroviral medicines to developing countries - Brenda Waning; Ellen Diedrichsen; Suerie Moon (Journal of the International AIDS Society, 2010)
Background Indian manufacturers of generic antiretroviral (ARV) medicines facilitated the rapid scale up of HIV/AIDS treatment in developing countries though provision of low‐priced, quality‐assured medicines. The legal framework in India that facilitated such production, however, is changing with implementation of the World Trade Organization Agreement on Trade‐Related Aspects of Intellectual Property Rights, and intellectual property measures being discussed in regional and bilateral free trade agreement negotiations. Reliable quantitative estimates of the Indian role in generic global ARV supply are needed to understand potential impacts of such measures on HIV/AIDS treatment in developing countries. Methods We utilized transactional data containing 17,646 donor‐funded purchases of ARV tablets made by 115 low‐ and middle‐income countries from 2003 to 2008 to measure market share, purchase trends and prices of Indian‐produced generic ARVs compared with those of non‐Indian generic and brand ARVs. Results Indian generic manufacturers dominate the ARV market, accounting for more than 80% of annual purchase volumes. Among paediatric ARV and adult nucleoside and non‐nucleoside reverse transcriptase inhibitor markets, Indian‐produced generics accounted for 91% and 89% of 2008 global purchase volumes, respectively. From 2003 to 2008, the number of Indian generic manufactures supplying ARVs increased from four to 10 while the number of Indian‐manufactured generic products increased from 14 to 53. Ninety‐six of 100 countries purchased Indian generic ARVs in 2008, including high HIV‐burden sub‐Saharan African countries. Indian‐produced generic ARVs used in first‐line regimens were consistently and considerably less expensive than non‐Indian generic and innovator ARVs. Key ARVs newly recommended by the World Health Organization are three to four times more expensive than older regimens. Conclusions Indian generic producers supply the majority of ARVs in developing countries. Future scale up using newly recommended ARVs will likely be hampered until Indian generic producers can provide the dramatic price reductions and improved formulations observed in the past. Rather than agreeing to inappropriate intellectual property obligations through free trade agreements, India and its trade partners ‐ plus international organizations, donors, civil society and pharmaceutical manufacturers ‐ should ensure that there is sufficient policy space for Indian pharmaceutical manufacturers to continue their central role in supplying developing countries with low‐priced, quality‐assured generic medicines.